2002
DOI: 10.1080/j.1600-0412.2002.811112.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-analyzes based on a prospective, randomized study comparing laparoscopic colposuspension with a tension-free vaginal tape procedure

Abstract: Cost-analyzes based on a prospective, randomized study comparing laparoscopic colposuspension with a tension-free vaginal tape procedure.Persson, Jan; Teleman, Pia; Etén-Bergquist, Christina; Wölner-Hanssen, PålPublished in: Acta Obstetricia et Gynecologica Scandinavica DOI: 10.1034/j. 1600 -0412.2002 .811112.x Published: 2002 Link to publication Citation for published version (APA): Persson, J., Teleman, P., Etén-Bergquist, C., & Wölner-Hanssen, P. (2002). Cost-analyzes based on a prospective, randomized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…This remained the case in the longer term of up to 8 years where Paraiso et al reported TVT and laparoscopic Burch colposuspension continued to have similar rates of cure (RR, 1.18; 95% CI, 0.36‐3.81). One trial reported reoperation rates at 1 year, with three out of 38 women in the TVT group and one out of 32 woman in the laparoscopic colposuspension group undergoing repeat surgery for “noncure.” They reported no difference in the perioperative complication rates between laparoscopic colposuspension and vaginal sling procedures (RR, 0.99; 95% CI, 0.60‐1.64) but surgical outcome measures, specifically length of hospital stay and return to normal activities, favored the MUS group …”
Section: Mus Compared To Other Continence Proceduresmentioning
confidence: 99%
“…This remained the case in the longer term of up to 8 years where Paraiso et al reported TVT and laparoscopic Burch colposuspension continued to have similar rates of cure (RR, 1.18; 95% CI, 0.36‐3.81). One trial reported reoperation rates at 1 year, with three out of 38 women in the TVT group and one out of 32 woman in the laparoscopic colposuspension group undergoing repeat surgery for “noncure.” They reported no difference in the perioperative complication rates between laparoscopic colposuspension and vaginal sling procedures (RR, 0.99; 95% CI, 0.60‐1.64) but surgical outcome measures, specifically length of hospital stay and return to normal activities, favored the MUS group …”
Section: Mus Compared To Other Continence Proceduresmentioning
confidence: 99%
“…Persson et al compared the costs of the LC and TVT procedures. They used sutures instead of mesh in the laparoscopic procedure (15). They found that LC was less expensive than the TVT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A total of seven trials were identified from the search, all of which were randomised control trials involving laparoscopic colposuspension and TVT in each of the arms, so were included in this review. The characteristics of these seven trials are displayed in Table 2 11–17 . One study had published versions in both English and Italian languages 11 .…”
Section: Resultsmentioning
confidence: 99%